Ontology of social interaction ethics in Al-Adab Al-Mufrad by using semantic web / Saidah Nafisah Mazli Sham - Mazli Sham, Saidah Nafisah (2016)
Social interaction is an exchange interaction of acts, actions or practices between one another. When it comes for social interaction ethics, it will bring another term or meaning. Without the social interaction ethics, there is a possibility that interaction with other people may bring any social harm or others. One of the ways we can learn about social interaction ethics is from hadith. Hadith is the collection reports of what the Prophet Muhammad said and did during his lifetime. Hadith has been labelled as one of the major source of guidance for Muslims beside Al-Quran. In each of hadith contain every aspect about human life. Unfortunately, because there are so many hadiths, it become difficult for people to make hadith as a reference, because it will be time consuming. In addition, Ethics is important because the serious problem that Muslims are facing is the absence of ethics in life, social matter and also relate to technology issues. The scope for this project are hadith in Al – Adab Al – Mufrad where the keyword of ethics in social interaction were identified and ontology was constructed. Ontology is knowledge of representation and declaration of formal specification of particular term and relation among them. Next, semantic web is developed to test the functionality of system where all the ethics and social interaction related to hadith are displayed. Detailed Research Methodology is chosen as the methodology for this project because this methodology is suitable in creating project that are more on research form. There are planning, information gathering, data collection and analysis, design, implementation and testing. For future recommendation, the ontology will be displayed in tree (OntoGraf), multi-language and instead of focusing on social interaction, in future ontology for the whole book of Al – Adab Al – Mufrad will been included.